Temporal dynamics of carbon storage in a Mediterranean mountain scrubland managed by prescribed fire - Fonseca, Felícia (2022)
Farmland abandonment and reduction of grazing activity, mainly in mountain areas with remote access and ageing population, have been contributing to shrub encroachment in such territories and, consequently, to increase fuel load available for triggering wildfires. Accordingly, it is necessary to use vegetation management practices in order to reduce wildfire risk, prescribed fire being one of the most common techniques used in the Mediterranean region. This research focused in the effects of a prescribed fire (PF) applied in Montesinho Natural Park (PNM), NE Portugal, on the temporal dynamics of carbon storage in mineral soil, litter layer (organic horizon), and shrub biomass. Before PF and thirty-six months after PF, aboveground shrub biomass was collected in areas of 1 m2 in 11 plots randomly distributed in the experimental shrub area. Also, in the same plots, litter thickness was measured and soil samples were collected before, two, six and thirty-six months after PF, in order to assess carbon concentration, bulk density and coarse elements content. Despite low to moderate fire intensity, carbon storage changes were observed in all compartments evaluated. Thirty-six months after PF, carbon storage in aboveground biomass of shrub species (7.4 Mg C ha- 1) was roughly two-thirds of that recorded prior to PF, and in litter layer (1.6 Mg C ha- 1) it was about half of that in the original situation (before PF). In contrast, the mineral soil showed a 10% carbon increase (6.4 Mg C ha- 1). Based on the balance between losses (shrub species and litter layer) and gains (mineral soil), at the end of the monitoring period (36 months), there was an annual positive rate of carbon storage, equivalent to 0.2 Mg C ha-1 year- 1. Even after anthropogenic disturbances, such as prescribed fire, shrub communities constitute important terrestrial carbon pools; hence, these ecosystems might play an important role in mitigating climate change.